2011
DOI: 10.1016/j.mce.2011.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Distinct regulation of B-type natriuretic peptide transcription by p38 MAPK isoforms

Abstract: Persistent controversy underlies the functional roles of specific p38 MAPK isoforms in cardiac biology and regulation of hypertrophy-associated genes. Here we show that adenoviral gene transfer of p38β but not p38α increased B-type natriuretic peptide (BNP) mRNA levels in vitro as well as atrial natriuretic peptide mRNA levels both in vitro and in vivo. Overexpression of p38α, in turn, augmented the expression fibrosis-related genes connective tissue growth factor, basic fibroblast growth factor and matrix met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 48 publications
3
23
0
1
Order By: Relevance
“…Direct injections of adenoviruses expressing p38α or p38β into the left ventricular wall of adult rats demonstrated that p38α stimulates fibrosis-related factors whereas p38β attenuated the ET-1-induced expression of the B-type natriuretic peptide. These findings indicate that p38α participates in the regulation of fibrotic remodeling process, and p38β stimulates the agonist-induced activation of the B-type natriuretic peptide and, thereby, elicits inhibitory effects on growth factors (Koivisto et al, 2011). DN-p38α transgenic mice exhibited cardiac hypertrophy despite the reduced p38α activity (Braz et al, 2003, Zhang et al, 2003).…”
Section: Mapks In Chronic Cardiac Stress (Hypertrophy and Heart Famentioning
confidence: 94%
“…Direct injections of adenoviruses expressing p38α or p38β into the left ventricular wall of adult rats demonstrated that p38α stimulates fibrosis-related factors whereas p38β attenuated the ET-1-induced expression of the B-type natriuretic peptide. These findings indicate that p38α participates in the regulation of fibrotic remodeling process, and p38β stimulates the agonist-induced activation of the B-type natriuretic peptide and, thereby, elicits inhibitory effects on growth factors (Koivisto et al, 2011). DN-p38α transgenic mice exhibited cardiac hypertrophy despite the reduced p38α activity (Braz et al, 2003, Zhang et al, 2003).…”
Section: Mapks In Chronic Cardiac Stress (Hypertrophy and Heart Famentioning
confidence: 94%
“…The MKK3b, MKK6b and WT p38β adenoviruses have been described previously [20]. The ATF3–overexpressing adenovirus (serotype 5) was generated as previously described [21].…”
Section: Methodsmentioning
confidence: 99%
“…GATA4 is phosphorylated at Ser105 by both ERK and p38,21, 22, 23 regulating its DNA‐binding activity and transcriptional activity 22, 23, 24, 25, 26. In addition to GATA4, a number of other transcriptional regulators, such as nuclear factor of activated T‐cells (NFAT), NKX‐2.5, Elk‐1, activator protein 1, myocardin, serum response factor, and nuclear factor kappa B, have been shown to participate in transcriptional regulation of BNP 20, 27, 28, 29, 30, 31, 32. Several studies have also indicated a central role for M‐CAT element, a thyroid‐responsive element and shear stress‐responsive element on the BNP promoter regulating BNP transcriptional activity 33, 34, 35, 36.…”
Section: Regulation Of Anp and Bnp Gene Expressionmentioning
confidence: 99%